Prognostic models to predict survival in patients with pancreatic cancer: a systematic review. Issue 8 (August 2022) - Ioannou, Liane J.; Maharaj, Ashika D.; Zalcberg, John R.; Loughnan, Jesse T.; Croagh, Daniel G.; Pilgrim, Charles H.; Goldstein, David; Kench, James G.; Merrett, Neil D.; Earnest, Arul; Burmeister, Elizabeth A.; White, Kate; et al.
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) has poor survival. Current treatments offer little likelihood of cure or long-term survival. This systematic review evaluates prognostic models predicting overall survival in patients diagnosed with PDAC. Methods: We conducted a comprehensive search of eight electronic databases from their date of inception through to December 2019. Studies that published models predicting survival in patients with PDAC were identified. Results: 3297 studies were identified; 187 full-text articles were retrieved and 54 studies of 49 unique prognostic models were included. Of these, 28 (57.1%) were conducted in patients with advanced disease, 17 (34.7%) with resectable disease, and four (8.2%) in all patients. 34 (69.4%) models were validated, and 35 (71.4%) reported model discrimination, with only five models reporting values >0.70 in both derivation and validation cohorts. Many (n = 27) had a moderate to high risk of bias and most (n = 33) were developed using retrospective data. No variables were unanimously found to be predictive of survival when included in more than one study. Conclusion: Most prognostic models were developed using retrospective data and performed poorly. Future research should validate instruments performing well locally in international cohorts and investigate other potential predictors of survival.